Back Cover: Controllable Galvanic Synthesis of Triangular Ag–Pd Alloy Nanoframes for Efficient Electrocatalytic Methanol Oxidation (Chem. Eur. J. 24/2015). Issue 24 (8th June 2015) - Xu, Lin; Luo, Zhimin; Fan, Zhanxi; Yu, Sijia; Chen, Junze; Liao, Yusen; Xue, Can
<x xml:space="preserve">Abstract</x> Triangular Ag–Pd alloy nanoframes can be synthesized through galvanic replacement by using Ag nanoprisms as sacrificial templates. The obtained triangular Ag–Pd alloy nanoframes exhibit superior electrocatalytic activity for methanol oxidation compared with the commercial Pd/C catalyst owing to the alloyed Ag–Pd composition as well as the hollow‐framed structures. This work could have a high impact on the rational design of future bimetallic alloy nanostructures with high catalytic activity for fuel cell systems. For more details see the Communication by L. Xu, C. Xue, et al. on page 8691 ff.